The effect of wet suit use by triathletes: an analysis of the different phases of arm movement - Hue, O.; Benavente, H.; Chollet, D. (Journal of Sports Sciences, 2003)
We analysed stroke phases and arm and leg coordination during front crawl swimming with and without a wet suit. Twelve nationally and internationally ranked French male triathletes performed three swim trials in randomized order using the front crawl stroke with and without a wet suit. All triathletes swam at three different swim velocities, corresponding to the paces appropriate for the 800 m (V800), 100 m (V100) and 50 m (V50) events. The different stroke phases and arm and leg coordination were identified by video analysis. Arm coordination was quantified using a new index of coordination, which expresses the three major modalities of opposition, catch-up and superposition in swimming. At all swim velocities, no significant differences in leg movements with or without the wet suit were noted. However, the wearing of the wet suit was associated with a significantly greater stroke length at the paces appropriate for the 100 and 50 m events (+3.46% and +3.10% at V100 and V50, respectively; P<0.01); a significantly greater stroke index at all three velocities (+5.18%, +5.21% and +5.91% at V800, V100 and V50, respectively; P<0.01); a significantly shorter pulling phase (-10.97%; P<0.05) and lower index of coordination (-21.87%; P<0.01) at the pace appropriate for the 800 m; and a significantly greater entry and catch phase (+9.81%; P<0.05) at the pace appropriate for the 100 m. We conclude that the wet suit amplified the coordination mode of the triathletes (i.e. catch-up coordination) without modifying stroke rate, recovery phase or leg movements.